The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jpln.201800398
|View full text |Cite
|
Sign up to set email alerts
|

Silicon mitigates boron deficiency and toxicity in cotton cultivated in nutrient solution

Abstract: Silicon (Si) application, both via foliar application and via roots, may be promising to improve plant growth under different biotic or abiotic stresses. In the present study, we investigated whether application of Si can also mitigate the harmful effects of boron (B)‐related nutritional disorders, such as B deficiency, when the application of B is inefficient or insufficient, and B toxicity, when the soil presents high levels of B. This may enable producers to apply Si preventively, if there is a low availabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 26 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…In addition, NH + 4 can be absorbed through aquaporins, non-selective cation transporters and K transporters, increasing the risk of exposure to excess NH + 4 concentrations (Bittsánszky et al, 2015). In this context, the toxicity of NH + 4 results in a lower accumulation of cations such as K, Ca and Mg (Nasraoui-Hajaji & Gouia, 2014), as observed in this study (Figure 1c-e). Since K + and NH + 4 are very similar in terms of valence and ionic radius, they may not be distinguishable by the membrane-bound carrier.…”
Section: Plants Have Developed Mechanisms To Avoid Nh +supporting
confidence: 67%
See 2 more Smart Citations
“…In addition, NH + 4 can be absorbed through aquaporins, non-selective cation transporters and K transporters, increasing the risk of exposure to excess NH + 4 concentrations (Bittsánszky et al, 2015). In this context, the toxicity of NH + 4 results in a lower accumulation of cations such as K, Ca and Mg (Nasraoui-Hajaji & Gouia, 2014), as observed in this study (Figure 1c-e). Since K + and NH + 4 are very similar in terms of valence and ionic radius, they may not be distinguishable by the membrane-bound carrier.…”
Section: Plants Have Developed Mechanisms To Avoid Nh +supporting
confidence: 67%
“…For example, accumulator plants, which actively absorb Si, exhibit Si contents greater than 10 g/kg while intermediate plants, which passively absorb Si, maintain Si contents between 5 and 10 g/kg and Si‐excluding plants have Si contents below 5 g/kg (Ma & Takahashi, 2002). The benefits of Si in cotton plants were to alleviate boron deficiency and toxicity (Souza Junior et al, 2019) and nickel toxicity (Khaliq et al., 2016). However, information on the role of Si on N deficiency and NH4+ toxicity in cotton plants is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade, researchers have assessed the effects of Si under excess boron (B), mainly in soil-grown cereals [ 64 , 65 , 66 , 67 ]. A recent study showed that Si application alleviated the harmful effects of B deficiency and toxicity in cotton by different modes of Si application [ 68 ]. The authors showed that foliar Si application was effective under B deficiency, by improving the photosynthesis-related parameters, while root application of Si restricted B transport into shoots under B toxicity.…”
Section: Si and Micro-nutrient Deficiency Or Heavy Metal Toxicitymentioning
confidence: 99%
“…In addition, B deficiency decreases the transport of photoassimilates from leaves to flowers and fruits, impairing flower, seed and fruit formation [ 8 ]. Although B plays a vital role in plant reproduction [ 9 ], micronutrient deficiency can also impair the vegetative development of cotton plants [ 10 ]. This developmental impairment is due to the boron’s function in the cell wall structure, as well as due to its biological function in the metabolism of nucleic acids, proteins, phenols and in the functionality of the plasma membrane and sugar transport [ 11 – 14 ], cell elongation, and protein synthesis, resulting in increased cell division [ 15 ].…”
Section: Introductionmentioning
confidence: 99%